2014
DOI: 10.4103/0259-1162.143152
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between Truview PCD laryngoscope and Macintosh laryngoscope in viewing glottic opening and ease of intubation: A crossover study

Abstract: Background:TruviewPCD laryngoscope is specially designed to aid positioning of the endotracheal tube as well as to record entry of the tube into glottis. Aim of the study is to compare the view of glottic opening and ease of intubation between TruviewPCD laryngoscope and Macintosh laryngoscope in patients undergoing general anesthesia (GA).Methodology:Two hundred patients undergoing elective surgery, under GA were randomized into two groups, Group TV and Group ML. In Group TV, TrueviewPCD laryngoscope was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…[ 8 ] Trueview video laryngoscope has an integrated optical lens system with unique angulated blade which provides optimal indirect view of the glottis. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Trueview video laryngoscope has an integrated optical lens system with unique angulated blade which provides optimal indirect view of the glottis. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also found decreased stress response to laryngoscopy with video laryngoscopes as compared to the Macintosh laryngoscope. [ 19 ] This finding could be because laryngoscopy can be performed with less lifting force required with video laryngoscopes as discussed previously.…”
Section: Discussionmentioning
confidence: 88%
“…in their comparison of Truview PCD and the Macintosh laryngoscope for glottic view and ease of intubation where they noted a significant rise from baseline HR with the Macintosh laryngoscope than with the Truview PCD laryngoscope. [ 13 ] Cierniak et al . observed that King Vision had comparative hemodynamic parameters with other video laryngoscopes.…”
Section: Discussionmentioning
confidence: 99%